RANCANG BANGUN MESIN PENEPUNG TIPE DISK MILL UNTUK SERAT TANDAN KOSONG KELAPA SAWIT SEBAGAI BAHAN BAKU BIOPELET - Muhammad Vogel Austen Kartamanggala (2023)
Oil palm empty bunches (EFB) are solid waste generated from the palm oil production industry. This waste consists of unused fiber and bunch kernels, this waste is usually burned or disposed of in vacant land. Utilizing the fiber of empty palm oil bunches can help reduce the volume of waste produced. One form of processing OPEFB fiber waste is as fuel in the form of biopellets. This study aims to design and build a disk mill type flour mill machine for empty palm fiber fruit bunches that can produce fine flour as raw material for biopellets with a capacity of more than 10 kg/hour. The research methods starts from design, manufacturing process to machine trials. The result of this research is a disk mill type flouring machine for OPEFB fiber with an overall machine dimension of 530x200x550 mm, using a 1 HP 1400 RPM motor with pulley transmission and can flour 10,84 kg/hour with a fineness of 20 mesh.